Analisis Fraud Hexagon dan Capital Turnover dalam Mendeteksi Kecurangan Laporan Keuangan Sektor Perbankan BEI Periode 2021-2023 - Aprilia, Alfi Noor; Martini, Tina (Jurnal Ekonomi dan Bisnis Islam, 2026)
AbstractThis study aims to examine the effect of fraud hexagon elements, namely financial target, financial stability, ineffective monitoring, change in auditor, change in director, CEO photo, and collusion, as well as capital turnover on fraudulent financial reporting in banking sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. This research employs a quantitative approach using secondary data obtained from companies’ annual reports. The sampling technique used is purposive sampling, resulting in 114 observations from 38 companies over three years. The data were analyzed using panel data regression with a random effect model. Fraudulent financial reporting is measured using the F-Score model. The results indicate that financial target and financial stability have a positive and significant effect on fraudulent financial reporting. Meanwhile, ineffective monitoring, change in auditor, change in director, CEO photo, collusion, and capital turnover do not have a significant effect. These findings suggest that internal pressure is the primary driver of fraudulent financial reporting compared to governance and managerial characteristics. This study contributes to the literature by extending the fraud hexagon model through the inclusion of capital turnover in the context of the Indonesian banking industry.Keywords: Fraudulent Financial Reporting; Fraud Hexagon; Financial Target; Financial Stability; Capital Turnover. AbstrakPenelitian ini bertujuan untuk menganalisis pengaruh elemen dalam fraud hexagon, yaitu financial target, financial stability, ineffective monitoring, change in auditor, change in director, foto CEO, dan collusion, serta capital turnover terhadap kecurangan laporan keuangan pada perusahaan sektor perbankan yang terdaftar di Bursa Efek Indonesia (BEI) periode 2021–2023. Penelitian ini menggunakan pendekatan kuantitatif dengan data sekunder yang diperoleh dari laporan tahunan perusahaan. Teknik pengambilan sampel menggunakan purposive sampling, sehingga diperoleh 114 observasi dari 38 perusahaan selama tiga tahun. Metode analisis yang digunakan adalah regresi data panel dengan model random effect. Kecurangan laporan keuangan diukur menggunakan model F-Score. Hasil penelitian menunjukkan bahwa financial target dan financial stability berpengaruh positif dan signifikan terhadap kecurangan laporan keuangan. Sementara itu, ineffective monitoring, change in auditor, change in director, foto CEO, collusion, dan capital turnover tidak berpengaruh signifikan. Temuan ini mengindikasikan bahwa tekanan internal perusahaan menjadi faktor utama yang mendorong terjadinya kecurangan laporan keuangan dibandingkan faktor tata kelola dan karakteristik manajerial. Penelitian ini memberikan kontribusi dalam pengembangan literatur terkait fraud hexagon dengan menambahkan variabel capital turnover dalam konteks industri perbankan di Indonesia. Kata Kunci: Kecurangan Laporan Keuangan; Financial Target; Fraud Hexagon.